Pengaruh Kualitas Produk Halal dan Strategi Promosi Islam terhadap Volume Penjualan pada Sentra Industri Dodol Tunas Mandiri Kecamatan Rimbo Bujang - Rinda Ristiana; Maulana Yusuf; Habriyanto Habriyanto (Lembaga Yasin AlSys, 2025)
The quality of halal products and promotional strategies based on Islamic principles are crucial factors in enhancing consumer appeal and increasing sales volume, particularly in industries targeting markets sensitive to product halalness. However, limited attention has been given to the influence of these factors within the local industrial sector. This study aims to analyze the effects of halal product quality and Islamic promotional strategies on sales volume at the Sentra Industri Dodol Tunas Mandiri, Rimbo Bujang District. A quantitative approach was employed by distributing questionnaires to 198 respondents selected through probability sampling, based on Krejcie and Morgan’s formula from a population of 406 individuals. Data were analyzed using SEM-PLS 4.0. The results indicate that halal product quality has a positive and significant effect on sales volume by strengthening product image and credibility. Furthermore, Islamic promotional strategies also exert a positive and significant influence on sales volume, as they attract consumers who emphasize halal aspects. These findings suggest that improving halal product quality and optimizing Islamic promotional strategies represent strategic measures for producers to sustainably increase sales volume.